2012
DOI: 10.1128/jb.06130-11
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Forming Acetyl Coenzyme A Synthetase in the Outermost Membrane of the Hyperthermophilic Crenarchaeon Ignicoccus hospitalis

Abstract: c Ignicoccus hospitalis, a hyperthermophilic, chemolithoautotrophic crenarchaeon was found to possess a new CO 2 fixation pathway, the dicarboxylate/4-hydroxybutyrate cycle. The primary acceptor molecule for this pathway is acetyl coenzyme A (acetylCoA), which is regenerated in the cycle via the characteristic intermediate 4-hydroxybutyrate. In the presence of acetate, acetylCoA can alternatively be formed in a one-step mechanism via an AMP-forming acetyl-CoA synthetase (ACS). This enzyme was identified after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 72 publications
(76 reference statements)
3
20
0
Order By: Relevance
“…Recently, it was shown that the ATP-consuming reaction of ACS could be coupled to ATP-producing processes, a possibility that gives interesting perspectives regarding further research on anammox carbon metabolism (Mayer et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was shown that the ATP-consuming reaction of ACS could be coupled to ATP-producing processes, a possibility that gives interesting perspectives regarding further research on anammox carbon metabolism (Mayer et al 2012). …”
Section: Resultsmentioning
confidence: 99%
“…acetate, succinate) are possible. One such reaction could be already confirmed (Mayer et al 2012): In the presence of acetate, acetyl-CoA is formed in a one-step mechanism via an AMP-forming acetyl-CoA synthetase (ACS). This enzyme was identified to be also located at the OCM of I. hospitalis (Fig.…”
Section: Energy Conservationmentioning
confidence: 95%
“…Therefore, it can be concluded that in I. islandicus and I. pacificus the OCM is energized. Furthermore, the acetyl-CoA synthesis of all members of the genus Ignicoccus is associated with the OCM (Mayer et al 2012), demonstrating that the extraordinary location of these enzymes or enzyme complexes is a common feature of all members the genus Ignicoccus. In contrast, the pore-forming complex Ihomp1 is exclusively found on the cell surface of I. hospitalis.…”
Section: Situation In Other Ignicoccus Speciesmentioning
confidence: 98%
“…Recent characterizations of two acetyl-CoA synthetases (ACS) from Ignicoccus hospitalis [26] and Pyrobaculum aerophilum [27] have uncovered novel structural adaptations, namely, a difference in oligomeric state from that of the mesophilic variants. Compared to their mesophilic counterparts, these hyperthermophilic enzymes form octomers whereas the aforementioned mesophiles follow the general trend of being monomers or homodimers.…”
Section: Thermophilic Proteinsmentioning
confidence: 99%